PELAKSANAAN ASURANSI KEBAKARAN PADA PT. JASINDO TAKAFUL CABANG PEKANBARU - Moch. H. Cahyana Maulana; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The interrelationship between the insurer in this case PT. Jasindo Takaful Branch Pekanbaru and the insured parties as service users created rights and obligations for each party, but in practice the loss of baggage that causes damage to the passenger without realizing the rights of passengers as appropriateThe purpose of this study, to determine bagaimankah implementation of fire insurance on PT.Jasindo Takaful, to determine the obstacles or barriers to the implementation of fire insurance PT. Jasindo Takaful branch Pekanbaru. To know the efforts to be made by the customer to fire at. Jasindo Takaful branch Pekanbaru.This type of research is a sociological research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at PT. Jasindo Takaful branch Pekanbaru, while the sample population is a whole party with regard to the problems examined in penelitiaan this, the data source used, primary data, secondary data and data tertiary, data collection techniques in this study with interviews, filling the questionnaire, and literature study.Implementation of fire insurance on PT. Jasindo Takaful using the principle of Mudharabah (profit sharing) and wakalah principle (keep or surrender). Fire insurance implementation constraints on PT. Jasindo Takaful Branch Pekanbaru is later than the insured party provides the information required to make the process of compensation and depreciation problems. Efforts to be made by the customer to fire at. Jasindo Takaful Pekanbaru branch is to provide information related to losses suffered by the insured.To the PT. Jasindo Takaful Pekanbaru Branch in order to implement the claims process is always guided by the policies and legislation so that no insured disadvantaged and in doing his duty is to bear the risk of the insured in order meminimalisis depreciable there so it does not harm the insured, To the insured, in order to inform each case which occurred in a timely manner so that any claims paid on time.